A review: Novel trends in hulled wheat processing for value addition. (December 2020) - Kulathunga, Jayani; Reuhs, Bradley L.; Simsek, Senay
Abstract: Background: Hulled wheat species have gained increasing attention since several studies have suggested that they could present a healthier and a better nutritional profile than modern wheat. Therefore, hulled wheat species are of interest for producing health beneficial food products and also, they can be found as whole grain products. Scope and approach: To gain the promising health benefits of ancient wheat, it is important to develop novel formulations and enhance the utilization of these wheat species. Review of the feasibility of producing novel hulled wheat products and discussion of the perspectives of the hulled wheat cultivation and processing which will aid in developing the future of the hulled wheat market. This review summarizes the processing of ancient wheat species, providing a summary of the studies that have thus far been published and sections are broken down into different products such as pan bread, specialty bread, pasta, breakfast cereals, and other baked goods, and beverages. Key findings and conclusions: In conclusion, the rediscovery of ancient wheat species offer new opportunities for farmers, millers, and bakers to produce specialty products that are associated with numerous health benefits. However, research efforts are essential to screen and assess ancient wheat species for breeding and processing to produce products with excellent nutritional and sensory properties. Graphical abstract: Image 1 Highlights: The increasing interest of consumers shown in natural and organic products has led to the reintroduction of hulled wheat. Underutilized hulled wheat can serve as a valuable raw material to produce a variety of food products. Hulled wheat products such as bulgur, grunken, sourdough bread, non-durum pasta, and breakfast cereals will aid in expanding the hulled wheat market. Research and breeding efforts are still needed to assess the genetic diversity of hulled wheat for their proposed health benefits.